2022
DOI: 10.1007/s13384-022-00553-0
|View full text |Cite|
|
Sign up to set email alerts
|

Teacher of mathematics identity as a predictor of teacher wellbeing

Abstract: This article reports on original research investigating teacher wellbeing while teaching mathematics in relation to teacher identity. Using survey data from mathematics teachers (N = 402) participating in a teacher of mathematics support initiative, teacher wellbeing was operationally defined as the experience of wellbeing whilst teaching, allowing an applied understanding of wellbeing in relation to the activity of teaching. Teacher identity was construed from prior research by the authors (Willis et al., in:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Researchers have demonstrated that teacher' well-being can be defined as a combination of personal professional achievement, satisfaction, purpose and happiness; it is constructed in the process of collaboration with colleagues and students; and it is related to teachers' environment and interactions with other people in the work environment (Acton and Glasgow, 2015;Brady and Wilson, 2021;McLellan and Steward, 2015). In addition, researchers have focused on the different impact dimensions of teacher well-being, including workload, individual pressure, relationship between teacher and students, work climate, accountability, job satisfaction, selfefficacy, professional identity and so on (Brady and Wilson, 2021;Collie et al, 2015;Fernandez-Chung and De Zoysa, 2022;Yeigh et al, 2022). Diener et al (2009) identified two new measures of well-being and combined psychology and social well-being theory to create psychosocial flourishing measurements to help assess individual levels of well-being.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have demonstrated that teacher' well-being can be defined as a combination of personal professional achievement, satisfaction, purpose and happiness; it is constructed in the process of collaboration with colleagues and students; and it is related to teachers' environment and interactions with other people in the work environment (Acton and Glasgow, 2015;Brady and Wilson, 2021;McLellan and Steward, 2015). In addition, researchers have focused on the different impact dimensions of teacher well-being, including workload, individual pressure, relationship between teacher and students, work climate, accountability, job satisfaction, selfefficacy, professional identity and so on (Brady and Wilson, 2021;Collie et al, 2015;Fernandez-Chung and De Zoysa, 2022;Yeigh et al, 2022). Diener et al (2009) identified two new measures of well-being and combined psychology and social well-being theory to create psychosocial flourishing measurements to help assess individual levels of well-being.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, researchers have focused on the different impact dimensions of teacher well-being, including workload, individual pressure, relationship between teacher and students, work climate, accountability, job satisfaction, self-efficacy, professional identity and so on (Brady and Wilson, 2021; Collie et al. , 2015; Fernandez-Chung and De Zoysa, 2022; Yeigh et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%